Optimalisasi Saluran Komunikasi Digital dan Tradisional oleh Dinas Komunikasi dan Informatika Kabupaten Bolaang Mongondow Selatan untuk Menjangkau Masyarakat dengan Melek Digital Terbatas - Gobel, Muhamad Risky Syawal; Isa, Rusli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research examines the communication strategy of the Bolsel District Communication and Informatics Office (Diskominfo) in integrating digital (website, social media) and traditional channels (face-to-face meetings, mosque loudspeakers) to reach the entire community. The objective is to develop an inclusive communication model that overcomes the digital divide, thereby ensuring equitable access to information and more effective government governance. This qualitative study analyzes the optimization of communication channels by Diskominfo in the context of limited public digital literacy. Primary data from in-depth interviews and secondary data were analyzed using triangulation. Through the application of Miles and Huberman's interactive model of analysis, the findings were reduced, presented, and verified to obtain a comprehensive contextual understanding. The findings indicate that Diskominfo Bolsel implements a hybrid communication strategy, combining digital channels (such as social media) with traditional ones (such as sub-district head visits and community forums). The role of community leaders as key gatekeepers, who filter information, enhances credibility and feedback. This strategy accommodates digital infrastructure limitations by leveraging existing social structures, aligning with Rogers' Diffusion of Innovations theory. The South Bolmong government successfully enhanced public communication with this hybrid model, which integrates platforms like Facebook and WhatsApp with conventional methods. However, challenges related to infrastructure and human resource capacity still need to be addressed to expand reach and inclusivity.